Taxonomy of some species from section Bromopsis (genus Bromus, Poaceae) in the flora of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
This publication is a result of studying the species from the section Bromopsis Dumort. (genus Bromus L.) in the flora of Ukraine with basal persistent fibrous reticulum. This is a complex of morphologically very similar taxa, which have been described after fragmentation of the well-known species Bromus cappadocicus Boiss. & Balansa and B. riparius Rehmann. As a result, five new species from Ukraine within the genus Bromopsis (Dumort.) Fourr. (≡section Bromopsis of the genus Bromus): Bromopsis glabrata Klokov, B. cimmerica Klokov, B. calcarea Klokov, B. pseudocappadocica Klokov, B. heterophylla (Klokov) Holub (basionym Zerna heterophylla Klokov) were described by M.V. Klokov. The differences between these species are rather insignificant. The rank of the taxa is unstable and varies from species to subspecies and varietas within the Bromopsis riparia (Rehmann) Holub (≡Bromus riparius Rehmann) and Bromopsis tomentella (Boiss.) Holub (≡Bromus tomentellus Boiss; ≡Zerna tomentella (Boiss.) Nevski). The presence of the Bromus cappadocicus in the flora of Ukraine is the subject of discussion. The main diagnostic features of the group are the morphological features of the basal fibrous reticulum, the length of the spikelets, the presence and shape of the awns, as well as the peculiarity of pubescence at the leaf blades and spikelets. We are studied authentic specimens and protologues. The features of these species, including diagnostic are overlaping. Only two features can be differentiated within the group. The first is a pubescence of the leaf blades. It splits into pubescence leaves and glabrous (or almost glabrous) leaves. The second is a biomorphological character of the rhizomes. The taxonomic revision within the group was conducted on the basis of the analysis on these features. The species Bromopsis glabrata, B. cimmerica, B. calcarea, B. pseudocappadocica, B. heterophylla should be reduced to the synonyms of Bromus cappadocicus and B. riparius. Previously, we defined the specimen KW010011888 as a holotype of Zerna heterophylla, which after finding the true holotype in LE (with the author's "Type") should be considered as isotype (Art. 9.5 ICN).
Keywords: nomenclature, type, holotype, lectotype, Bromeae, Zerna.